THE COMPETITIVENESS OF AGRICULTURAL PRODUCT AND INPUT MARKETS: A REVIEW AND SYNTHESIS OF RECENT RESEARCH. (29th December 2016) - SHELDON, IAN M.
Abstract: This article reviews literature on competitiveness of agricultural product and input markets. Although researchers in the United States and Europe emphasize different stages of the agricultural and food marketing system, their focus is similar: extent of buyer power, although both have largely ignored the sector supplying inputs to agriculture. The key conclusion is that there is little robust empirical evidence for food processing firms exerting buyer power, and there are limited data concerning vertical contracts between food processing and agriculture, but there is a small body of evidence concerning food retailer behavior and vertical coordination between food retailing and processing.